Interplay of art and faith in women's communities. Developing a heightened awareness of research perspectives and evolving methodologies - Markowska, Anna (2024)
The Lost and Found: Revising Art Stories in Search of Potential Changes marked the inaugural conference of a collaborative initiative between the University of Wroclaw, Universidade Nova de Lisboa and the Polish Institute for World Art Studies in Warsaw. This unique meeting brought together university researchers and artists, creating a stimulating atmosphere. The collaborative artistic endeavours undertaken aimed to build community and explore alternative knowledge production rooted in affectivity and openness to surprise, rather than an immediate quest for success. The focus was on a shared experience of being together and learning about each other’s roles beyond the conventional boundaries of scholars and artists. At the heart of the conference was the project Residua of Pre-Modern Relations with Art in Selected Contemporary Convents in Lesser Poland and Lower Silesia, supported by the National Science Centre in Warsaw.Although the residues and anachronisms discussed during the meeting did not explicitly refer to religious orders, they provided insights into the significance of faith and the evolving nature of the sacred in contemporary art. The project’s premise challenged the distinction between the religious and the spiritual, emphasizing the roles of community, respect, and care. It was hypothesized that female religious orders maintain these values in relation to theplace of art in everyday life. Consequently, if an art historian wishes to study the relationship between women’s art and the sacred in everyday life, they should learn from nuns and female artists, not merely study them.
Keywords: religia; sztuka duchowa; żeńskie klasztory; spoleczności; budowanie wiedzy; feminizm; konferencje naukowe